2008
DOI: 10.1002/gps.2098
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess attitudes, behaviors, and inter‐office communication by psychiatrists and primary care providers in the care of older adults with schizophrenia

Abstract: Our preliminary findings indicated more favorable attitudes and behaviors by PCPs than had been anticipated based on earlier research with younger patients. The data suggest that the failure of older schizophrenia patients to receive adequate treatment may not be due primarily to clinicians' negative attitudes and behaviors, and that problems with communication may play a more important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
3
10
0
Order By: Relevance
“…Lastly, dimension 3 (Training) would include specifically perceptions of the level of knowledge to treat schizophrenia and other psychotic disorders (23, 25), the usage of neuroleptic drugs (8) as well as the training level in psychiatry (15). The dimensions included in the questionnaire line up with other research in which these factors also appear as the ones that weigh most heavily in the treatment of people with mental disorders in general and schizophrenia in particular (Aragonés et al, 2011;Carr et al, 2004;Jones et al, 2009;Oud et al, 2007;Verdoux et al, 2006). The results of the internal consistency analysis show low values in general, for the complete scale as well as for the 3 dimensions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Lastly, dimension 3 (Training) would include specifically perceptions of the level of knowledge to treat schizophrenia and other psychotic disorders (23, 25), the usage of neuroleptic drugs (8) as well as the training level in psychiatry (15). The dimensions included in the questionnaire line up with other research in which these factors also appear as the ones that weigh most heavily in the treatment of people with mental disorders in general and schizophrenia in particular (Aragonés et al, 2011;Carr et al, 2004;Jones et al, 2009;Oud et al, 2007;Verdoux et al, 2006). The results of the internal consistency analysis show low values in general, for the complete scale as well as for the 3 dimensions.…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, among the professionals' factors that can influence the treatment of people with mental disorders in general and with schizophrenia in particular we can find three groups of factors. The first group includes the communication and quality of the collaboration between primary care and the mental health services (Aragones, Piñol, LopezCortacans, Hernández & Caballero, 2011;Carr et al, 2004;Jones, Vahia, Cohen, Hindi & Nurhussein, 2009;Meadows, Harvey, Joubert, Barton & Bedi, 2007;Oud, Schuling, Slooff & Meyboom-de Jong, 2007;Verdoux, Cougnard, Grolleau, Besson & Delcroix, 2006). In a second group we can find those that encompass the beliefs and attitudes of GPs towards mental illness (McCab & Leas, 2008;Nkire et al, 2015;Oud et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…physicians showing the same level of stigma towards such people as those in the general population (Jones, et al, 2009). Jones, et al (2009, in a survey of 24 primary care providers and 27 psychiatrists in New York, found that both groups had slightly negative stereotypes and attitudes toward older adults with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, women with schizophrenia are less likely to marry, bear children, and raise their own children than are women in the general population (Dickerson, 2007). Older adults with schizophrenia have increased mortality that may be due to a variety of factors, such as patient characteristics, attitudes of health care providers, and institutional factors (Jones, et al, 2009 Medical classifications represent a specific set of predetermined defined symptoms and duration that are useful for informing pharmacological treatment protocols. They may not be as helpful, however, in providing meaningful understanding of a person's experiences, as there is a great deal of variability in how symptoms present in individuals across the lifespan (Collier, 2007).…”
Section: Schizophrenia and Older Peoplementioning
confidence: 99%
“…Failure of the psychiatric consultant to adhere to them can lead to an unpleasant and unhelpful experience for other members of the team (22). This is important to consider, as historically psychiatrists have been perceived by primary care providers as being unavailable (23) and perhaps unwilling (24) to provide consultation. The process of indirect consultation not only builds the capacity of the behavioral health provider and the primary care provider to treat mental health conditions but also promotes the development of trusting relationships between all team members.…”
Section: The Psychiatrist's Roles In the Collaborative Care Modelmentioning
confidence: 99%